Electromagnetic interference induced ventricular tachycardia in left ventricular assist device. Issue 12 (23rd July 2022) - Chatta, Payush; Grewal, Dennis; Ali, Saif; Garg, Jalaj; Mandapati, Ravi; Contractor, Tahmeed; Bhardwaj, Rahul
Abstract: Left ventricular assist devices (LVAD) have been increasingly utilized end‐stage heart failure despite guidelinedirected medical therapy (due to limited organ availability) as a bridge to transplant or destination therapy, with improved overall survival.Majority of patients undergoing LVAD implantation have pre‐existing implantable cardioverter‐defibrillator (ICD) in‐situ.We present a case of device‐device interaction resulting in EMI inducing recurrent inappropriate device therapies inducing ventricular arrhythmia followed by the inappropriate triggering of noise reversion mode, thereby inhibiting device therapies.With the increase in number of end‐stage heart failure patients with ICDs in situ (and limited organ availability) undergoing LVAD implantation, it is imperative to recognize potential device‐device interactions to avoid unwarranted invasive interventions.